2020
DOI: 10.1021/acssuschemeng.0c03211
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanochemical Solid-State Synthesis of Silver Nanoparticles with Antibacterial Activity Using Lichens

Abstract: A completely solid-state mechanochemical synthesis of silver nanoparticles overcoming the problem with water insolubility of lichen metabolites hampering their use for the classical green synthesis in water is shown herein. Four lichen species (Xanthoria elegans, Cetraria islandica, Usnea antarctica, and Leptogium puberulum) and AgNO3 were used as reducing agents and Ag(0) precursor, respectively. The reaction progress was rapid in the first two cases, whereas in the case of U. antarctica and L. puberulum, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 62 publications
(64 reference statements)
0
20
0
2
Order By: Relevance
“…The biosynthesis of lichen-derived nanoparticles is gaining popularity these days: as the process does not involve use of any toxic chemicals, therefore, they can be safely used as pharmaceuticals (Kowalski et al, 2011). Researchers around the globe have been following different methodologies such as biomechanical and chemical solid-state synthesis for the synthesis of lichen-based nanoparticles (Baláž et al, 2020). Mie et al (2014) reported the synthesis of silver nanoparticles by the reduction of silver nitrate using aqueous extract of the lichen Parmotrema praesorediosum as a reductant as well as a stabilizer.…”
Section: Lichen-derived Nanoparticles: Methodologies and Approachesmentioning
confidence: 99%
See 4 more Smart Citations
“…The biosynthesis of lichen-derived nanoparticles is gaining popularity these days: as the process does not involve use of any toxic chemicals, therefore, they can be safely used as pharmaceuticals (Kowalski et al, 2011). Researchers around the globe have been following different methodologies such as biomechanical and chemical solid-state synthesis for the synthesis of lichen-based nanoparticles (Baláž et al, 2020). Mie et al (2014) reported the synthesis of silver nanoparticles by the reduction of silver nitrate using aqueous extract of the lichen Parmotrema praesorediosum as a reductant as well as a stabilizer.…”
Section: Lichen-derived Nanoparticles: Methodologies and Approachesmentioning
confidence: 99%
“…The characterization of nanoparticles, so formed, was carried out using techniques such as TEM, scanning electron microscopy (SEM), XRD, and FT-IR. Baláž et al (2020) reported the solid-state mechanochemical synthesis of silver nanoparticles using lichens Xanthoria elegans, C. islandica, Usnea antarctica, and Leptogium puberulum. The method involved milling of lichen sample and silver nitrate together in a pulverisette.…”
Section: Lichen-derived Nanoparticles: Methodologies and Approachesmentioning
confidence: 99%
See 3 more Smart Citations